Dietary vitamin E intake and risk of Parkinson's disease: a cross-sectional study - Hao, Xiaoqian; Li, Haiyan; Li, Qinglian; Gao, Da; Wang, Xiaoling; Wu, Chunxiao; Wang, Qizhang; Zhu, Meiling (Frontiers in Nutrition, 2024)
Objective: Current evidence on the association between dietary vitamin E intake and the risk of Parkinson's disease (PD) is limited. The aim of the study was to explore the association of dietary vitamin E intake with PD in the United States among adults over 40 years.We conducted a cross-sectional study with data collected from National Health and Nutrition Examination Survey (NHANES) from 2009 to 2018. A total of the sample of 13340 participants were included. To identify the different characteristics of the participants, we utilized propensity score matching (PSM) to reduce the effects of selection bias and confounding variables. Weighted univariate and multivariable logistic regression were used to examine the association between dietary vitamin E intake and PD before and after matching. Then, restricted cubic spline (RCS) was used to visually describe the possible non-linear relationships.Finally, we employed the subgroup analysis to further investigate the relationship between dietary vitamin E intake and PD.Results: According to the weighted univariate and multivariable logistic regression analysis, vitamin E intake was inversely associated with the risk of PD before and after matching. The results of RCS analysis revealed no non-linear inverse relationship between vitamin E intake and PD before and after matching. The subgroup analysis showed that age may influence the negative association between 2 vitamin E and PD (P < 0.05 for interaction). Conclusion: Among participants over 40 years of age, vitamin E intake was negatively associated with the risk of PD. Our data may support the supplementation of vitamin E to be used as an intervention strategy for the occurrence of PD.